PENGARUH PELAKSANAAN PEMBELAJARAN TATAP MUKA TERBATAS BERBASIS KONTEKSTUAL PADA PEMBELAJARAN BIOLOGI TERHADAP HASIL BELAJAR PESERTA DIDIK - Satriani Satriani (Program Studi PGSD Universitas Flores, 2022)
Indonesia is one of the countries that has an impact on the occurrence of the COVID-19 pandemic. Aspects of life are also disrupted because this has no impact on the education aspect.. As a result, learning in schools, which were usually done offline, is now being done online. However, since July 2021 through a decree from the Minister of Education and Culture, limited face-to-face learning (PTM) has been implemented. This study aims to determine the effect of the implementation of contextual-based limited face-to-face learning on Biology learning on the learning outcomes of students in class X IPA MA Pest Al Qamar. This research uses ex post facto research. Data collection techniques using questionnaires to see the implementation of contextual-based face-to-face learning and documentation to see student learning outcomes. The results obtained are the implementation of contextual-based limited face-to-face learning has been carried out very well with an average score of 3.69, and student learning outcomes are in the good category with an average score of 3.14. The results of statistical correlation analysis obtained the value of r2 of 0.446 or 44.6%. Based on these results, it can be concluded that there is an effect of implementing contextual-based limited face-to-face learning with biology learning outcomes for Class X IPA MA Pest Al Qamar.